Dynamics Of Social, Economic, Educational, And Religious Changes During The Covid-19 Pandemic - Syahrul Isan; Hastra Mawijaya; Syahrul Kiram (Yayasan Yusda Edu Indonesia, 2026)
ABSTRACT The COVID-19 pandemic has become a major global event that has changed many aspects of people's lives, including social, economic, educational, and religious aspects. This study aims to explore the changes that occurred during the pandemic and their impact on people's lives. The method used is a literature study with a descriptive qualitative approach, collecting data from various sources such as books, scientific journals, reports from official institutions, and other relevant sources. The study shows that the pandemic has changed the way people interact socially, as the use of digital technology has become more frequent and intense. The pandemic has led to a decline in economic activity and an increase in the number of unemployed people, but it has also accelerated the shift towards a digital economy. In education, direct learning has shifted to online learning systems, which has presented several challenges, such as differences in access to technology and a decline in the quality of learning interactions. Meanwhile, in religious life, there have been changes in the way worship and religious activities are carried out using digital media, but this has not diminished the spiritual values ​​held by the community. This study shows that the COVID-19 pandemic has acted as a trigger for social change, accelerating people's ability to adapt to technological developments and forming new lifestyles that are likely to persist after the pandemic ends.